Neurospora chromosome rearrangements with mutant phenotypes provide an opportunity to sequence breakpoint junctions - David D. Perkins (Fungal Genetics Reports, 1995)
Present knowledge of junction sequences is inadequate for understanding how chromosome rearrangements originate. In N. crassa, cloned segments are known to cover breakpoints of T(IR->VIR)UK-T12 (Asch et al. 1992 Genetics 130:737-748), T(VR;VIL)mpr15-2 am (E.B. Cambareri and J. A. Kinsey, personal communication), T(IR;IIR)4637 al-1 (Schmidhauser et al. 1990 Mol. Cell. Biol. 10:5064-5070), T(IR->VII;I;IV)AR173 (Kang and Metzenberg 1990 Mol. Cell Biol. 10:5839-5848; S. D. Haedo, personal communication), T(IR->VII)TM429 his-3 (Catcheside and Angel 1974 Aust. J. Biol. Sci. 27:219-229; Legerton and Yanofsky 1985 Gene 39:129-140, T(VIL->IR)IBj5 cpc-1 (Paluh et al. 1990 Genetics 124:599-606), T(IR->VL)AR190 (Butler 1992 Genetics 131:581-592), and T(IIL->IIIR)AR18 and T(IIL->VI)P2869 (M. L. Smith and N. L. Glass, personal communication). However, nucleotide sequencing across junctions has been accomplished only for the first two.